PENGARUH PEMANFAATAN ARTIFICIAL INTELLIGENCE, KEGIATAN LITERASI DIGITAL, DAN PENGGUNAAN APLIKASI GOOGLE CLASSROOM TERHADAP KEAKTIFAN SISWA XI MPLB SMKN 25 JAKARTA - Aryo Sadewo; Marsofiyati; Mayang Riyantie (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the influence of Artificial Intelligence utilization, digital literacy activities, and Google Classroom application usage on student engagement among Grade XI Office Management and Business Services (MPLB) students at SMKN 25 Jakarta. The research employed a quantitative approach using explanatory causal research design. Data collection was conducted by distributing questionnaires to respondents. The study population consisted of 72 Grade XI MPLB students at SMKN 25 Jakarta for the 2025/2026 academic year, and a total sampling technique was applied, in which the entire population was used as the research sample. Data were analyzed using IBM SPSS Statistics version 29 through descriptive statistical analysis, instrument testing, classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination analysis. The findings indicate that Artificial Intelligence utilization has a positive and significant effect on student engagement, with a t-value of 5.500, exceeding the t-table value of 1.995, and a significance level of <0.001. Digital literacy activities also have a positive and significant effect on student engagement, with a t-value of 3.146 and a significance level of 0.002. Furthermore, Google Classroom application usage has a positive and significant effect on student engagement, with a t-value of 5.147 and a significance level of <0.001. Simultaneously, the three independent variables have a positive and significant effect on student engagement, with an F-value of 39.662, exceeding the F-table value of 2.740, and a significance level of <0.001. The coefficient of determination (R Square) of 0.636 indicates that Artificial Intelligence utilization, digital literacy activities, and Google Classroom application usage jointly explain 63.6% of the variance in student engagement, while the remaining 36.4% is explained by other factors outside the scope of this research.